Protease Enzyme Supplementation in Weaning Piglets Fed Reduced Crude Protein Diets: Effects on Gut Health Integrity and Performance Response - Furlani, Nathana Rudio; Da Motta, Stephane Alverina Briguente; Ramos, Bruno Teixeira; Fernandes, Wender Vieira; de Farias, Maria Rogervânia Silva; Riveros, Rony [UNESP]; Tizziani, Tarciso; Hannas, Melissa Izabel (MDPI, 2025)
Two trials evaluated the effects of dietary protease inclusion in weaned piglets fed diets with or without crude protein (CP) reduction, focusing on performance, intestinal health, and amino acid digestibility. In Trial I, 270 piglets (21-63 days) received six treatments: control (PC), PC with 100 g/ton protease A (PC+A), CP reduced by 1.0% (NC1) or 1.5% (NC1.5), NC1.5 with 50 g/ton protease A (NC1.5+A), and NC1.5 with 50 g/ton protease B (NC1.5+B). PC+A improved weight gain, feed intake, and feed conversion compared with NC1.5+A. The incidence of diarrhea was reduced in animals fed protease-supplemented diets (PC+A, NC1.5+A and NC1.5+B). PC had greater ileal villus height than NC1.5+B, and PC+A showed a higher jejunal villus-to-crypt ratio than reduced CP groups. NC1.5+B increased jejunal expression of IL-6, TNF-α, and haptoglobin. In Trial II, 12 ileal-cannulated piglets received diets with or without protease A. Protease improved the standardized ileal digestibility (SID) of methionine+cysteine and tryptophan but reduced the SID of glycine and proline. While protease supplementation can improve some amino acids (Met+Cys and Thr) protein digestibility, our findings suggest it cannot fully replace careful amino acid balancing in CP-reduced diets. However, protease-supplemented diets were associated with improved intestinal morphometry and a reduced incidence of diarrhea.